Nyai as Caregivers: Their Role in Fostering Discipline and Moral Values in Islamic Boarding Schools - Herlina; Musli; Boby Yasman Purnama (Journal of Educational Management Research, 2026)
This study aims to analyze the role of nyai in the caregiving and character development of students in Islamic boarding schools. This research employs a qualitative method with a descriptive approach. Data were collected through observations, interviews, and documentation involving the nyai as the primary caregiver, along with selected students and administrators. The data were analyzed through data reduction, data display, and conclusion drawing, while validity was ensured through source and technique triangulation. The findings reveal that: (1) the nyai plays a significant role in fostering students’ moral development through role modeling, discipline enforcement, daily supervision, and religious guidance; (2) several challenges emerge, including students’ lack of discipline, diverse backgrounds and personalities, and limited communication between students and caregivers; (3) to address these challenges, the nyai implements continuous guidance, persuasive approaches, improved communication, and strengthened supervision alongside positive habit formation. The study implies that the nyai holds a central role in shaping students’ character, enhancing discipline, and internalizing religious values, highlighting the importance of adaptive caregiving strategies in Islamic educational settings.